The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s10616-014-9799-8
|View full text |Cite
|
Sign up to set email alerts
|

GRP78 regulates sensitivity of human colorectal cancer cells to DNA targeting agents

Abstract: This study was carried out to investigate the activation status of unfolded protein response (UPR) in colorectal cancer (CRC) and its contribution to CRC resistance to chemotherapy-induced apoptosis. Chemotherapy-induced apoptosis was assessed by the propidium iodide method. Activation of UPR was evaluated in CRC cell lines using immunoblotting technique and in CRC tissues using immunohistochemistry. Findings of the present study revealed that the UPR is constitutively activated in CRC cell lines and CRC tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
(41 reference statements)
2
20
0
Order By: Relevance
“… 45 For instance, increased expression levels of major actors of the UPR such as IRE1α, unspliced and spliced XBP1, PERK and ATF6 were observed in tissues sections from a variety of human tumors including brain, breast, gastric, kidney, liver, lung and pancreatic cancers ( Table 1 ). 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 Moreover, the chaperone GRP78 is also found overexpressed in many cancers 46 , 47 , 48 , 49 , 50 , 51 , 52 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 64 , 65 , 66 and is involved in the dissemination/metastasis of human tumors. GRP78 overexpression is associated with higher tumor grades and reduced patients’ survival.…”
Section: Upr Molecular Mechanisms and Their Functions In Cancers: Thementioning
confidence: 99%
“… 45 For instance, increased expression levels of major actors of the UPR such as IRE1α, unspliced and spliced XBP1, PERK and ATF6 were observed in tissues sections from a variety of human tumors including brain, breast, gastric, kidney, liver, lung and pancreatic cancers ( Table 1 ). 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 Moreover, the chaperone GRP78 is also found overexpressed in many cancers 46 , 47 , 48 , 49 , 50 , 51 , 52 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 64 , 65 , 66 and is involved in the dissemination/metastasis of human tumors. GRP78 overexpression is associated with higher tumor grades and reduced patients’ survival.…”
Section: Upr Molecular Mechanisms and Their Functions In Cancers: Thementioning
confidence: 99%
“…Moreover, ER stress may also trigger autophagy progression ( Yorimitsu et al , 2006 ; Ciechomska et al , 2013 ). Unfolded protein response signalling molecules, such as immunoglobulin heavy-chain binding protein (BIP; also known as GRP78 and HSP5A), heat shock protein 90 kDa beta (HSP90B1; also known as GRP94) and C/EBP homologous protein (CHOP; also known as DDIT3 and GADD153), have been reported to regulate the chemo- and radio-sensitivities of CRC cells ( Mhaidat et al , 2014 ; Drake et al , 2015 ), and to be correlated with CRC ( Rask et al , 2000 ; Xing et al , 2006 ; Takahashi et al , 2011 ). Notably, BIP, a key molecule in UPR signalling, has been identified as a novel predictive biomarker for CRC patients to receive adjuvant chemoradiotherapy ( Thornton et al , 2013 ; Lee et al , 2015 ).…”
mentioning
confidence: 99%
“… 11 In addition, a significant association was found between GRP78 expression and response to chemotherapy. 12 Moreover, GRP78 was found to be constitutively activated in CRC cell lines and CRC tissues isolated from patients. 26 Furthermore, levels of GRP78 were inversely associated with sensitivity of CRC cells to chemotherapy-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that transcriptional inhibition of GRP78 by siRNA increases in vitro and in vivo chemotherapy-induced cell death. 12 , 27 In addition, inhibition of GRP78 by using nucleoside analogs has been shown to inhibit cancer cell proliferation. 10 This was due to binding of these analogs to the ATPase domain of GRP78 and resulted in enhanced synthesis of procaspases, thus enhancing apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation